Valproic acid and bladder healing: an experimental study in rats - MARIA DE LOURDES PESSOLE BIONDO-SIMÕES; MOACIR OLIVEIRA DALL’ANTONIA; MATHEUS PRINCE GOEHR; RACHEL BIONDO-SIMÕES; SÉRGIO OSSAMU IOSHII; ROGÉRIO RIBEIRO ROBES (Revista do Colégio Brasileiro de Cirurgiões, 2022)
ABSTRACT Purpose: to recognize the effects of valproic acid (VPA), an epigenetic drug, on the bladder healing process, in rats. Method: twenty male Wistar rats were divided in two groups: experimental (A), treated with VPA (150mg/Kg/day), and control (B) with 0.9% sodium chloridrate. Healing was analyzed on the third and seventh days, evaluating the inflammatory reaction, collagen synthesis and angiogenesis. Results: inflammatory reaction on the third day was minimal and acute in both groups. On the seventh day, it was subacute in both groups, moderate intensity in group A and minimal in group B (p=0.0476). Collagen III intensity, marked by immunohistochemistry, was similar in both groups. Collagen I intensity on the third day was similar in both groups, but on the seventh day it was higher in experimental than control (p=0.0476). Collagen evaluation by picrosiriusred allowed to verify that the presence of collagen III was similar in both groups (p=0.3312) on the third day, and it was higher in control on the seventh day (p=0.0015). Collagen I showed similarity on the third day (p=0.3100), and it was higher in control on the seventh day (p=0.0015). Vessel marked with anti-SMA counting showed fewer vessels on the third (p=0.0034) and seventh day (p=0.0087) in experimental group. The lower intensity of angiogenesis was confirmed with anti-CD34, on the third day (p=0,0006) and on the seventh day (p=0,0072). Conclusion: VPA determined alterations in the bladder healing process, in rats, with lower collagen density and less angiogenic activity, but without compromising the integrity of the organ.